1992
DOI: 10.1080/02724936.1992.11747550
|View full text |Cite
|
Sign up to set email alerts
|

A study on delayed hypersensitivity to rotavirus in infancy and childhood

Abstract: The T-cell responsiveness to rotavirus antigen and phytohaemagglutinin (PHA) together with T-cell total and subsets quantitation was carried out in 50 non-diarrhoeal and six rotavirus diarrhoeal subjects. All individuals in the non-diarrhoeal group responded well to PHA and had normal values for T-cell subsets. The number of positive responders to the rotavirus antigen increased gradually from 0% in the newborns to 92% in older children. The increasing risk of exposure to rotavirus infection is thought to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Children with acute rotavirus diarrhea had more positive and significantly higher T-cell proliferation to rotavirus antigen compared to healthy children. Among healthy children, T-cell proliferation was absent in newborns, minimally present in children aged <6 months but became more commonly detected in older age groups of children [ 22 , 25 , 26 , 28 , 37 ]. In contrast to this, however, one study also reported evidence of detectable T-cell proliferation in newborn children [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children with acute rotavirus diarrhea had more positive and significantly higher T-cell proliferation to rotavirus antigen compared to healthy children. Among healthy children, T-cell proliferation was absent in newborns, minimally present in children aged <6 months but became more commonly detected in older age groups of children [ 22 , 25 , 26 , 28 , 37 ]. In contrast to this, however, one study also reported evidence of detectable T-cell proliferation in newborn children [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported a lower circulating frequency of CD4 + and CD8 + T-cells in response to acute rotavirus infection. In one study, while healthy children had normal proportions of CD3 + , CD4 + , and CD8 + T-cell subsets, children with acute rotavirus diarrhea had selectively lowered CD4 + T-cell proportion and a low CD4 + :CD8 + T-cell ratio [ 22 ]. A case study of a single child with rotavirus diarrhea showed a depressed CD4 + T-cell frequency and CD4 + :CD8 + ratio in an acute phase that persisted up to one-month post-infection but normalized by convalescent period [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation